The Dead Sea scrolls at Qumran and the concept of a library - Crawford, Sidnie White.; Wassen, Cecilia, 1962- (Studies on the Texts of the Desert of Judah, 2016)
The Dead Sea Scrolls at Qumran and the Concept of a Library presents twelve articles by renowned experts in the Dead Sea Scrolls and Qumran studies. These articles explore from various angles the question of whether or not the collection of manuscripts found in the eleven caves in the vicinity of Khirbet Qumran can be characterized as a "library," and, if so, what the relation of that library is to the ruins of Qumran and the group of Jews that inhabited them. The essays fall into the following categories: the collection as a whole, subcollections within the overall corpus, and the implications of identifying the Qumran collection as a library.